Ecological aspects on urban blowflies in midwest Argentinean Patagonia (Diptera: Calliphoridae) - Schnack, Juan Alberto (1998)
Based upon their species composition and numerical trends, two blowfly taxocoenoses from a dense urban settlement (eusynanthropy) and an isolated dwelling (hemisynanthropy) at Esquel, province of Chubut (43° S, 71 0 W) were surveyed and sampled during SpringSummer 1993-1994. Data show that despite the nearness of both study sites, their blowflies taxocoenosis exhibit different patterns of overall and species relative importance. Overall fly's capture was of 3,885 specimens. The highest number offlies was recorded injanuary at eusynanthropy, and from january to March at hemisynanthropy. In all cases, the second hourly sampling included more specimens than the remaining ones